2017
DOI: 10.1002/pd.4983
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydramnios in isolated oral cleft pregnancies: incidence and outcome in a retrospective study

Abstract: The incidence of idiopathic polyhydramnios in isolated OC pregnancies is 6.5%. Polyhydramnios in isolated OC increases the risk of palate involvement. The presence of polyhydramnios is not associated with adverse perinatal or long-term outcome. If isolated at prenatal assessment, polyhydramnios does not increase the risk of associated anomalies postpartum. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
(62 reference statements)
1
5
2
Order By: Relevance
“…Aviram et al, (2015) disagree with the current study statistically not significant gender with AFV, Male 54.4%in polyhydramnios, male 51.1% in normal AFV. The study disagrees with the present study statistically no significant between baby gender and AFV; Male in normal AF was 62.8%, polyhydramnios was 60.0%, female in normal AF was 37.2%, and polyhydramnios was 40% (Depla et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Aviram et al, (2015) disagree with the current study statistically not significant gender with AFV, Male 54.4%in polyhydramnios, male 51.1% in normal AFV. The study disagrees with the present study statistically no significant between baby gender and AFV; Male in normal AF was 62.8%, polyhydramnios was 60.0%, female in normal AF was 37.2%, and polyhydramnios was 40% (Depla et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Examples of the latter are Ebstein anomaly, ventricular septal defect, anterior ectopic anus, and oesophageal atresia [31][32][33][34] . Similar anomalies were not detected before birth in two recent studies, indicating the limitations of ultrasound in pregnancy 18,28 .…”
Section: Discussionsupporting
confidence: 71%
“…The present study data confirm these findings, as the frequency of additional anomalies increased with involvement of the alveolus and the palate. Only this study and the study by Depla et al 28 have reported the prenatal diagnoses of CL, CLA, and CLAP subdivisions, suggesting differences in the prevalence of additional anomalies.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In addition, the detection of other findings such as severe oligohydramnios/anhydramnios or polyhydramnios in association with genitourinary tract malformations, central nervous system anomalies, micrognathia, abnormal posturing of fetal limbs, or orofacial/neck/thoracic tumoral masses makes the diagnosis straightforward in most cases (Figure 3), lowering the likelihood of esophageal atresia in the differential diagnosis. Of note, a fetal cleft lip with or without cleft palate or cleft palate may theoretically affect swallowing 18 . However, in our experience, no case of a small or absent stomach was associated with this orofacial anomaly.…”
Section: Resultsmentioning
confidence: 47%